The field guide to the north american teenager ebook - Philippe, Ben (2024)
William C. Morris YA Debut Award Winner! A hilarious YA contemporary realistic novel about a witty Black French Canadian teen who moves to Austin, Texas, and experiences the joys, clichés, and awkward humiliations of the American high school experience—including falling in love. Perfect for fans of Nicola Yoon, When Dimple Met Rishi , and John Green.  Norris Kaplan is clever, cynical, and quite possibly too smart for his own good. A Black French Canadian, he knows from watching American sitcoms that those three things don’t bode well when you are moving to Austin, Texas. Plunked into a new high school and sweating a ridiculous amount from the oppressive Texas heat, Norris finds himself cataloging everyone he meets: the Cheerleaders, the Jocks, the Loners, and even the Manic Pixie Dream Girl. Making a ton of friends has never been a priority for him, and this way he can at least amuse himself until it’s time to go back to Canada, where he belongs. Yet against all odds, those labels soon become actual people to Norris…like loner Liam, who makes it his mission to befriend Norris, or Madison the beta cheerleader, who is so nice that it has to be a trap. Not to mention Aarti the Manic Pixie Dream Girl, who might, in fact, be a real love interest in the making. But the night of the prom, Norris screws everything up royally. As he tries to pick up the pieces, he realizes it might be time to stop hiding behind his snarky opinions and start living his life—along with the people who have found their way into his heart.